Single Stem Silviculture - Sagreiya, K. P. (Indian Forester, 1946)
A method of tending irregular teak crops of coppice origin is described. The crop is considered ready for the first cleaning-cum-thinning operations when the ’declared’ stems have attained a height of 25 to 30 feet. All malformed shoots, interfering shrubs and bamboo regrowth are first cut back to facilitate working. After this cleaning, the best of the dominant stems, termed elites, are selected for retention and given the optimum growing space by felling the inferior dominant and dominated stems interfering with their crowns. By optimum growing space is meant a clear space round an elite, of radius R feet, where R is equal to the overbark, breast-height diameter of the stem in inches, plus 3. On the basis of this formula, the normal spacing between two adjacent stems of diameters D1 and D2 inches, is (D1 + D2+ 6) or say S feet. A variation of Â±2 feet is permitted. When the actual distance, say X, between two adjacnt stems is equal to (SÂ±2) feet these stems are considered ideally spaced and both are retained as elites. When X is less than (S - 2) feet, the stem of the smaller diameter is removed, as it is putting on lesser value increment. If the two stems are more or less equal in size, uniform spacing between retained stems is given prefernce over stem-quality. When X is more than (S+2) feet, a courtesy elite is retained between the two good dominants, or else reliance is placed on coppice from the cut-back stems, to prevent abnormal development of the elites, as also to fully utilise the intervening growing space. Suppressed stems are also retained as nurses to clean the boles of elites. Hence the name Single Stem Silviculture.